2015
DOI: 10.1161/circep.114.002195
|View full text |Cite
|
Sign up to set email alerts
|

Sympathetic Nerve Stimulation, Not Circulating Norepinephrine, Modulates T-Peak to T-End Interval by Increasing Global Dispersion of Repolarization

Abstract: Background T-peak to T-end interval (Tp-e) is an independent marker of sudden cardiac death. Modulation of Tp-e by sympathetic nerve activation and circulating norepinephrine (NE) is not well understood. The purpose of this study was to characterize endocardial and epicardial dispersion of repolarization (DOR) and its effects on Tp-e with sympathetic activation. Methods and Results In Yorkshire pigs (n=13), a sternotomy was performed and the heart and bilateral stellate ganglia (SG) were exposed. A 56-electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
72
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 93 publications
(85 citation statements)
references
References 42 publications
(45 reference statements)
6
72
0
1
Order By: Relevance
“…These authors further observed that application of the β-AR agonist isoproterenol also increased the DOR, but the spatial distribution of APD shortening was completely different, suggesting that the dramatic changes in repolarization observed with sympathetic nerve stimulation are due to heterogeneous nerve distribution. Similar results have been obtained in the porcine ventricles in which dramatically different spatial patterns of activation-recovery intervals (ARIs, surrogate measure for APD) and repolarization were observed in response to sympathetic nerve stimulation compared to circulating NE (Ajijola et al, 2013a; Yagishita et al, 2015). Furthermore, these investigators also found that nerve stimulation, but not NE infusion, increased the T-peak to T-end interval, which is an independent marker of sudden cardiac death (Yagishita et al, 2015).…”
Section: Ventriclesupporting
confidence: 79%
“…These authors further observed that application of the β-AR agonist isoproterenol also increased the DOR, but the spatial distribution of APD shortening was completely different, suggesting that the dramatic changes in repolarization observed with sympathetic nerve stimulation are due to heterogeneous nerve distribution. Similar results have been obtained in the porcine ventricles in which dramatically different spatial patterns of activation-recovery intervals (ARIs, surrogate measure for APD) and repolarization were observed in response to sympathetic nerve stimulation compared to circulating NE (Ajijola et al, 2013a; Yagishita et al, 2015). Furthermore, these investigators also found that nerve stimulation, but not NE infusion, increased the T-peak to T-end interval, which is an independent marker of sudden cardiac death (Yagishita et al, 2015).…”
Section: Ventriclesupporting
confidence: 79%
“…SGB may also be particularly useful for attenuating burst discharge activity in left stellate ganglion, which has been shown to precede most VT and sudden cardiac death in a canine model of ischemic cardiomyopathy (4243). Sympathoexcitation increases repolarization heterogeneity (4446), increases risk of delayed after depolarizations (47,48), and increases arrhythmia inducibility (49). It also modulates peri-infarct tissues harboring circuits capable of facilitating MMVT (50).…”
Section: Discussionmentioning
confidence: 99%
“…The right and left stellate ganglia were isolated behind the parietal pleura. Bipolar needle electrodes attached to a photoelectric isolation unit and Grass stimulator (Grass Technologies, S88 and PSIU6) were used for stimulation (54). The current required for a 10% increase in heart rate or systolic blood pressure at 4 Hz and 4 ms was defined as threshold.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, in infarcted hearts, bipolar voltage electroanatomic mapping was performed as described above, and location of each electrode overlying scar, border zone, or viable myocardium meticulously was noted. ARI was analyzed from unipolar electrograms of each electrode using iScaldyn (University of Utah, Salt Lake City, Utah, USA) (47,54,55). Briefly, activation time was defined from the origin to the minimum dV/dt of the activation wavefront of the unipolar electrogram, and recovery time was defined as the start of activation to the maximum dV/dt of repolarization wavefront.…”
Section: Methodsmentioning
confidence: 99%